The Influence of Anodization Time With The Electrochemical Cell Design on The Fabrication Process of Porous Silicon Nanostructures - Yaseen, Zainab Abduljabbar; Yiseen, Ghadah Abdaljabar (Iraqi Journal of Science, 2019)
The influence of anodization time with the electrochemical cell design on the fabrication process of porous silicon (PS) nanostructures based on two electrochemical anodization cells (designed single tank cell and double tank cell) with two anodization times (10 and 30 minutes) was studied. Atomic force Microscopy (AFM) characterization had revealed three types of pores, mesopores, mesopore fill of mesopores, and macropore fill of mesopores were obtained from designed single tank cell with (10 and 30 minutes) of anodization time, whilst for double tank cell has not revealed precise information about the size and type of pores. Pores formation have been further approved by current-voltage (I-V) measurement and photoluminescence emission by ultraviolet-lamp (254-366) nm for both electrochemical cells.